2020
DOI: 10.1371/journal.pone.0235458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 82 cases of death from COVID-19

Abstract: A recently developed pneumonia caused by SARS-CoV-2 bursting in Wuhan, China, has quickly spread across the world. We report the clinical characteristics of 82 cases of death from COVID-19 in a single center. Clinical data on 82 death cases laboratory-confirmed as SARS-CoV-2 infection were obtained from a Wuhan local hospital's electronic medical records according to previously designed standardized data collection forms. All patients were local residents of Wuhan, and a large proportion of them were diagnosed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
391
4
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(479 citation statements)
references
References 21 publications
36
391
4
18
Order By: Relevance
“…Zhang and colleagues 9 reported that the median age in a small cohort of COVID-19 non-survivors was 72.5, similar to our ndings. In addition, both Zhang and we found that male COVID-19 patients accounted for the majority of the non-survivors.…”
Section: Discussionsupporting
confidence: 91%
“…Zhang and colleagues 9 reported that the median age in a small cohort of COVID-19 non-survivors was 72.5, similar to our ndings. In addition, both Zhang and we found that male COVID-19 patients accounted for the majority of the non-survivors.…”
Section: Discussionsupporting
confidence: 91%
“…These factors could increase the likelihood of the development of endothelial dysfunction and platelet aggregation promoting the formation of occlusive thrombus in the heart and lungs in COVID-19 patients with diabetes. In patients with COVID-19 however there are increased levels of fibrinogen, CRP, and D-dimer (14,58), with elevated D-dimer levels being a risk factor for mortality (53) these findings indicate that there appears to be an increase not only in coagulation but also in fibrinolysis. An imbalance or an impairment of coordination between coagulation and fibrinolysis appears to be responsible for much of the pathology observed in COVID-19 (59).…”
Section: Obesity Diabetes Affect the Host Response To Sars-cov-2mentioning
confidence: 99%
“…While most patients are asymptomatic or display only mild symptoms such as fatigue, fever, and dry coughs, some individuals develop pneumonia, severe acute respiratory distress syndrome, sepsis, and septic shock with an overall case fatality rate of 5% (4)(5)(6). In a subset of patients, COVID-19 is associated with a so-called cytokine storm, lymphopenia, and dysregulation of the immune system, yet the underlying mechanisms and cellular sources of these immunological complications remain to be fully understood (7,8). First studies have shown that reduced T cell counts correlated with disease severity in COVID-19 patients (9).…”
Section: Introductionmentioning
confidence: 99%